CD60b: Enriching Neural Stem/Progenitor Cells from Rat Development into Adulthood - Fernanda Gubert; Camila Zaverucha-do-Valle; Michelle Furtado; Pedro M. Pimentel-Coelho; Nicoli Mortari; Ana C. M. Leão; Elize A. Hayashi; Alberto Nobrega; Rosalia Mendez-Otero; Marcelo F. Santiago (Stem Cells International)
CD60b antigens are highly expressed during development in the rat nervous system, while in the adult their expression is restricted to a few regions, including the subventricular zone (SVZ) around the lateral ventricles—a neurogenic niche in the adult brain. For this reason, we investigated whether the expression of C60b is associated with neural stem/progenitor cells in the SVZ, from development into adulthood. We performed in vitro and in vivo analyses of CD60b expression at different stages and identified the presence of these antigens in neural stem/progenitor cells. We also observed that CD60b could be used to purify and enrich a population of neurosphere-forming cells from the developing and adult brain. We showed that CD60b antigens (mainly corresponding to ganglioside 9-O-acetyl GD3, a well-known molecule expressed during central nervous system development and mainly associated with neuronal migration) are also present in less mature cells and could be used to identify and isolate neural stem/progenitor cells during development and in the adult brain. A better understanding of molecules associated with neurogenesis may contribute not only to improve the knowledge about the physiology of the mammalian central nervous system, but also to find new treatments for regenerating tissue after disease or brain injury.